Capturing and sharing open educational practices with eportfolios [electronic resource] - MERLOT (Multimedia Educational Resource for Learning and Online Teaching).; Skills Commons; The California State University; MERCED-I (Mindanao Educational Resources for Curricular Enhancement and Development-Initiatives) on OER (Open Educational Resources). (Long Beach, CA MERLOT, 2020)
Quoted from the homepage: The MERLOT community created a collection of online resources about ePortfolios that you can explore and learn about ways to capture Open Educational Practices with ePortfolios.MERLOT's Open Collection on ePortfolios Career Oriented ePortfolios Institutional ePortfolios Learning-centered ePortfolios Teaching-centered ePortfolios Assessment and Rubrics Pedagogies Resources Selecting and Using Tools Support and Training You are welcome and encouraged to contribute to this collection! You are also welcome and encouraged to explore our partner organizations, including AAEEBL (The Association for Authentic, Experiential, & Evidence-Based Learning).
mixed.
online.
Keywords: Electronic information resources; Internet research; Internet in higher education; Open learning; Education, Higher; Electronic books; College teaching -- Electronic portfolios. .; College teaching -- Aids and devices -- Electronic portfolios. .; Universities and colleges -- Curricula -- Aids and devices -- Electronic portfolios. .; Web-based instruction -- United States; Education, Higher -- United States -- Web-based instruction; Universities and colleges -- United States -- Web-based instruction